Metaphor on Three Poems, Invictus, The Road Not Taken and Dreams - Chandra Arya Pranata; Sunardi; A.K Amarullah (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2020)
This study presents an analysis of metaphor on three poems, Invictus, The Road Not Taken and Dreams. The objective of this study is: to find out the types and meaning from three poems. The analyses were based on the combination of Lakoff and Johnson’s theory (2003), and Konvecses’s theory (2010) to find out the kind’s of metaphor and meaning of Invictus, The Road Not Taken, and Dream poems. What is the kind’s of metaphor and meaning of line on Invictus, The Road Not Taken, and Dream poems. In this study, the researcher will use descriptive qualitative research. The findings of this study were directed to know what is the kind’s of metaphor and meaning of Invictus, The Road Not Taken, and Dream poems. The result of this research is to show that the kind’s of metaphor and the meaning of poetry